13. KNOWLEDGE AND PRACTICE OF HYPERTENSION PREVENTION AMONG THE CHAM PEOPLE IN BAC BINH DISTRICT, BINH THUAN PROVINCE, IN 2020 (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the knowledge and practice of preventing hypertension among the Cham people in Bac Binh district, Binh Thuan province, in 2022. Methods: A cross-sectional study was conducted on 535 Cham people 18 or older at 3 communes in Bac Binh district, Binh Thuan province, in 2022. Results: The percentage of Cham people with correct general knowledge about hypertension was 32.3%, and correct general practice about hypertension prevention was 23.4%. Of which 74% had not smoked, 84.7% had not abused alcohol, 51.8% had not eaten salty food, 91.2% had eaten low fat, 29.4% had eaten enough fruits and vegetables, and 77% had done physical activity. Conclusion: It is necessary to promote communication to raise awareness about hypertension prevention by using more Cham language and changing risk behaviors in Cham people to improve health.
Keywords: Knowledge, practice, hypertension, Cham ethnic people.